Analisis Shouryakugo dalam Anime "Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi" Episode 1-3 - Yudha Pratama, Cahyabayu Dimas; Khasanah, Umul (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research focuses on analyzing the formation process of shouryakugo (word shortening) in the anime “Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi” episodes 1-3. The purpose of this research is to identify the types of shouryakugo found in the anime "Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi" episodes 1-3 and to understand the process of their formation. The theory underlying this research is the shouryakugo formation theory according to Kindaichi, which classifies shouryakugo into several types based on their formation process. This research method uses a morphological approach, aiming to provide an in-depth explanation of the form changes and types of shouryakugo in the anime "Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi" episodes 1-3. Data were collected through dialogues in the anime "Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi" episodes 1-3 using the listening and note-taking technique. The results of this research found a total of 14 shouryakugo data in the anime "Keikenzumi na Kimi to Keiken Zero na Ore ga Otsukiai suru Hanashi" episodes 1-3, including 8 geryaku and 6 fukushiki shouryaku.